Linking Local and Global Sustainability - Sandhu, Sukhbir; McKenzie, Stephen; Harris, Howard; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The book takes a holistic approach to sustainability. Acknowledging the Brundtland definition, that sustainable development meets the needs of the present without compromising the ability of future generations to meet their own needs, the book is specifically concerned with the ethics of contemporary social and environmental sustainability activity and thinking. It is concerned with the role of institutions–both local and global in achieving sustainability initiatives. All twelve chapters extend sustainability–conceptually, empirically and theoretically, and in doing so provide insights into linking local and global sustainability. The book refocuses sustainability as a series of interwoven and dynamic relationships, backed by just ethical decision-making, which begin locally, and reach out to impact the global level.
1 Introduction -- Part 1 -- 2 Sustainability, integrity and judgement; Chris Provis -- 3 Sustainability as a work of Justice; Howard Harris -- 4 Sustainable societies; Stephen McKenzie.-5 Sustainable organisational culture; Anke Arnaud -- 6 Sustaining organisations through knowledge sharing: changing the paradigm of power; Saras Sastrowardoyo -- 7 Building the Future by Looking to the Past: Examining Research Published on Organizations and the Environment.; Tima Bansal & Jijun Gao -- 8 Macintyre’s concept of practice in organisational behaviour: Do parallel constructs suggest interdisciplinary research for sustainability?; Erich Fein -- Part 2 Examples and cases --  9 Life Cycle Analysis and sustainable supply chain management;  Claudine Soosay & Andrew Fearne -- 10 Impact of FairTrade initiatives on individuals; Luciana Vieira -- 11 Exploration of corporate social responsibility (CSR) in multinational companies within the food industry; Padmakshi Rana -- 12 Life Cycle Analysis and sustained organisation change in auto repair shops; Barbara Resta -- 13 Indigenous perspectives on sustainability; Azmiri Mian & Kyle Powys Whyte -- 14 Sugar and spice and everything nice: exploring sustainability conflicts; Carmel Young, Sukhbir Sandhu and Howard Harris -- 15 Social sustainability of development projects; Vandra Harris -- 16 Conclusion -- 17 Bibliography -- Contributors.- Index.
Keywords: Environmental economics; Ethics; Quality of life; Environmental Economics; Ethics; Quality of Life Research